The Role of Nature Play in Supporting Students with ADHD According to Biblical Principles - Lin, Ivy Mary; Setia, Yulia; Puspitasari, Dani (Aletheia Christian Educators Journal, 2026)
As inclusive education expands, Christian schools are tasked with developing holistic pedagogies for students with ADHD. This research investigates nature play as a developmentally appropriate and theologically grounded approach. Framed by the Pyramid of Learning, which positions sensory integration as foundational to higher-order skills, the study explores how sensory-rich outdoor environments support children with ADHD in a Christian school setting. Using qualitative methods, including observation and teacher interviews, the research identifies how nature play fosters emotional regulation, sustained attention, and social interaction in these students. Furthermore, this practice aligns with core Christian values, embodying stewardship of creation and compassion, and affirming each child's identity as an image-bearer of God (Imago Dei). This study presents a model that synthesizes developmental theory and Christian pedagogy, demonstrating how faith-based schools can implement evidence-informed, spiritually coherent strategies. It highlights the potential of faith-based educational settings to implement evidence-informed, spiritually coherent strategies that support the holistic development of neurodiverse learners. In particular, this study will contribute to the existing literature on the implementation of inclusive education in Christian schools.